الفكر السياسي عند برهان غليون - لطرش وهيبة; اشراف: يوسف بوراس (جامعة محمد بوضياف المسيلة, 2025)
يعالج هذا البحث أطروحات المفكر السوري الفرنسي برهان غليون السياسيةالذيتدور حول بناء دولة مدنية ديمقراطية، تضمن الحقوق والحريات، وتقطع مع الاستبداد والتبعية. وقد شكّلت كتاباته مرجعًا مهمًا للحركات الديمقراطية في العالم العربي، رغم المصاعب التي واجهتها أفكاره عند التطبيق في ظل الأوضاع السياسية المعقدة. الكلمات المفتاحية:دولة مدنية، ديمقراطية، الاستبداد، التبعية. Abstract This research addresses the political theses of the Syrian-French thinker Burhan Galion, which revolves around building a democratic civil state that guarantees rights and freedoms and breaks with tyranny and subordination. His writings constituted an important reference for democratic movements in the Arab world, despite the difficulties his ideas faced when applied in light of complex political situations. Keywords: civil state, democracy, tyranny, subordination.